Peningkatan Kemampuan Literasi Digital Melalui Bina Kreativitas Smart Vloger Bagi Pemuda Karang Taruna Di Desa Pameuntasan Kecamatan Kutawaringin Kabupaten Bandung - Mariane, Ine; Indrianie, Mona (Fisip UIN Sunan Gunung Djati Bandung, 2025)
In today's digital era, digital literacy skills are a primary need for the younger generation, including in rural areas. However, youth from the Karang Taruna (Youth Organization) in Pameuntasan Village still tend to be passive consumers of social media, failing to utilize it creatively and productively. Meanwhile, the village's potential—including culture, tourism, and social activities—has not been optimally utilized as digital content. Therefore, a program is needed to encourage youth to become